Tradycyjna biżuteria tybetańska - Greniewska, Natalia Wiktoria (Studia Azjatystyczne, 2017)
The purpose of this paper is to present the phenomenon of Tibetan jewellery, its history, characteristics, styles, applied patterns and ornamentation. The work focuses on traditional jewellery, its application, execution methods, tools and materials used by jewellers, as well as on the symbolism, mainly Buddhist one, with broad meaning and often used during execution of the ornaments.